IRISIN AND INTERLEUKINS-33 AND -37 LEVELS IN PATIENTS WITH ISCHEMIC HEART DISEASE UNDER OBESITY INFLUENCE: IRISIN AND INTERLEUKINS-33 AND -37 AND ISCHEMIC HEART DISEASE - Kovalova, Yuliia (Medicinski časopis, 2021)
Objective. The aim of this work was to investigate the obesity influence on irisin and interleukins 33 and 37 levels in patients with coronary heart disease.Methods. The first group was pr esented by 36 patients with coronary artery disease (CAD) and obesity. The comparison group consisted of 33 patients with coronary artery disease with normal body weight. The control group included 30 practically healthy persons. The irisin and interleukins levels were measured by ELISA. Obesity was indicated as increased body mass index (BMI) ≥ 30 kg/m2.Results. The study showed that irisin was reduced 127.36 (107.52 – 137.88) ng / ml) in group with stable angina pectoris compared with the controls 147.92 (139.04 - 172.55) ng / ml, p = 0.290. Patients with combined coronary artery disease and obesity had significantly increased IL-33 levels (123.56 ± 32.38 pg / ml, p = 0.004) and IL-37 (131.74 ± 24.17 pg / ml, p = 0.004). Multivariate regression analyses showed that BMI positively correlated with the serum irisin in CAD obese patients (β = 0.255, p = 0.039).Conclusions. The coexistence of obesity in patients with stable angina is suggested to be significant factor of irisin diminishing and interleukins 33 and 37 levels increasing. Body mass index had direct correlation with the irisin concentrations in the obese patients with coronary artery disease.
Keywords: ischemic heart disease; angina pectoris; obesity; interleukin; irisin